Phylogenetic relationships among European ratsnakes of the genus Elaphe Fitzinger based on mitochondrial DNA sequence comparisons - Lenk, Peter; Joger, Ulrich; Wink, Michael (Amphibia-reptilia, 2001)
In order to elucidate the phylogenetic relationships in European ratsnakes of the genus Elaphe, we analyzed a 597 bp part of the mitochondrial cytochrome b gene of eight West Eurasian and one East Asian species. Lampropeltis served as outgroup. Maximum parsimony and maximum likelihood suggest the existence of four lineages: 1) E. scalaris; 2) the E. longissima species group comprising E. longissima, E. lineata, E. situla, E. hohenackeri, and E. persica; 3) E. quatuorlineata and 4) E. dione as a sister group to 3). Elaphe scalaris is basal and shows no closer affiliation with any other analyzed species. The Middle Eastern E. persica and E. hohenackeri appear basal within the E. longissima group. Elaphe lineata differs by 8% nucleotide substitutions from E. longissima, supporting the hypothesis that both taxa represent distinct species. Elaphe situla is associated with Elaphe longissima and E. lineata. Three analyzed subspecies of E. quatuorlineata are represented by distinct haplotypes. The extent of divergence gives reason to assign species status to the taxon sauromates. Besides, we found two very distinct haplotypes within the range of E. (q.) sauromates, indicating the existence of a third, so far unidentified, species within the E. quatuorlineata complex. The East Asian E. porphyracea clusters with the E. longissima group. This, as well as comparisons with supplementary sequences of Asian Elaphe species, document the multiple origins of European Elaphe. Um die phylogenetischen Beziehungen europäischer Kletternattern der Gattung Elaphe zu erhellen, sequenzierten und analysierten wir ein 597 Nukleotide messendes Stück des mitochondrialen Cytochrom b Gens von acht west-eurasischen und einer ostasiatischen Art. Lampropeltis diente als Außengruppe. Maximum parsimony und maximum likelihood Berechnungen zeigen die Existenz von vier genetischen Linien auf: a) E. scalaris; b) die E. longissima Artengruppe mit E. longissima , E. lineata, E. situla, E. hohenackeri, und E. persica; c) E. quatuorlineata und d) E. dione als Schwestergruppe zu c). Elaphe scalaris nimmt eine basale Position ein und scheint mit keiner untersuchten Art näher verwandt zu sein. Die westasiatischen Arten E. persica und E. hohenackeri sind die Schwestergruppe zu E. longissima, E. lineata und E. situla. Elaphe lineata unterscheidet sich durch 8% Nukleotidaustausche von E. longissima, wodurch der Artstatus von E. lineata unterstützt wird. Elaphe longissima, E. lineata und E. situla bilden eine Abstammungsgemeinschaft. Auch die Haplotypen der drei untersuchten E. quatuorlineata-Unterarten unterscheiden sich so stark, daß Artstatus für das Taxon sauromates zu fordern ist. Darüberhinaus fanden wir im Gebiet von E. (q.) sauromates zwei stark unterschiedliche Haplotypen, die die Existenz einer dritten bislang unidentifizierten Art nahelegen. Die ostasiatische E. porphyracea scheint der E. longissima-Gruppe nahe zu stehen. Dies, sowie der Vergleich mit ergänzenden Sequenzdaten asiatischer Elaphe-Arten, belegt den mehrfachen Ursprung europäischer Elaphe.